Assessing the impact of World War I on the City of London - Cochrane, S (University of Oxford, 2009)
The interwar years saw the rise of New York to challenge London as the world's leading provider of financial services. This paper will show that the current explanations fail to identify a key factor in New York's rise. The City was prevented from operating a full capacity by a capital issues embargo, imposed by the Bank of England to support the pound. As a result, New York was able to enter the sector with little competition from London, and expand rapidly to issue over half of the global capital exported abroad in the 1920s. Without the embargo, this would not have been possible, as the London merchant banks were the most productive producers in the industry, a position built up over the previous half century. This result challenges the consensus that the return to gold was good for the City. The merchant banks suffered and lost business, suggesting that this policy was even more disastrous than is currently thought.